Development of Novel Dengue NS1 Multiplex Lateral Flow Immunoassay to Differentiate Serotypes in Serum of Acute Phase Patients and Infected Mosquitoes - Lai, Szu-Chia; Huang, Yu-Yine; Wey, Jiunn-Jye; Tsai, Meng-Hung; Chen, Yi-Ling; Shu, Pei-Yun; Chang, Shu-Fen; Hung, Yi-Jen; Hou, Jiu-Nan; Lin, Chang-Chi (Frontiers in Immunology, 2022)
Dengue is among the most rapidly spreading arboviral disease in the world. A low-cost, easy to use point-of-care diagnostic tool for the detection and differentiation of dengue virus serotypes could improve clinical management, disease prevention, epidemiological surveillance, and outbreak monitoring, particularly in regions where multiple serotypes co-circulate. Despite widespread deployment, no commercial dengue antigen diagnostic test has proven effective in differentiating among dengue virus serotypes. In the current study, we first established mAb pairs and developed a multiplex lateral flow immunoassay for the simultaneous detection of the dengue viral NS1 antigen and identification of serotype. The proposed system, called Dengue serotype NS1 Multiplex LFIA, provides high sensitivity and specificity. In testing for JEV, ZIKV, YFV, WNV, and CHIKV, the multiplex LFIA gave no indication of cross- reactivity with cell culture supernatants of other flaviviruses or chikungunya virus. In analyzing 187 samples from patients suspected of dengue infection, the detection sensitivity for serotype D1 to D4 was 90.0%, 88.24%, 82.61%, and 83.33% and serotype specificity was 98.74%, 96.13%, 99.39%, and 97.04%, respectively. Our multiplex LFIA can also identify mono- and co-infection of different serotype of dengue viruses in mosquitoes. The proposed Multiplex LFIA provides a simple tool for the rapid detection of dengue serotypes and in the differential diagnosis of fever patients in regions where medical resources are limited and/or multiple DENVs co-circulate.